2021
DOI: 10.1007/s00404-021-06259-5
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID-19 pandemic on the rate of newly diagnosed gynecological and breast cancers: a tertiary center perspective

Abstract: Purpose The aim of the present study was to assess the impact of postponed screening examinations and lockdown measures on gynecological and breast cancer diagnoses throughout the year 2020 in a gynecological oncological center in Austria. Methods Data of 889 patients with either newly diagnosed gynecological or breast cancer between January 2019 and December 2020 were collected. Clinical parameters including symptoms, performance status, comorbidities and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Therefore, 33 reports consisting of 31 studies formed the basis of this review. 18 50 A PRISMA flow diagram outlining the screening process is presented in Figure 1 . The list of excluded studies with reasons of exclusion is reported in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, 33 reports consisting of 31 studies formed the basis of this review. 18 50 A PRISMA flow diagram outlining the screening process is presented in Figure 1 . The list of excluded studies with reasons of exclusion is reported in Supplementary Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…Reductions in the diagnosis rate of breast cancer were observed in all but one study, by Vardhanabhuti et al, 48 with reported rates ranging from 36.0% reduction to a 0.5% increase among registry-based studies 26 , 27 , 40 , 48 , 50 and 64.7% to 3.0% reduction in non-registry-based studies. 19 , 21 23 , 28 34 , 37 – 39 , 42 , 43 , 45 – 47 Figure 3 displays the results of the meta-analysis of the diagnosis rate ratios. Similar to the changes in mammogram screening rates, we noted an estimated 18% (RR: 0.82, 95% CI: 0.63–1.06) and 29% (RR: 0.71, 95% CI: 0.63–0.80) reduction in diagnosis rates between 2019 and 2020 based on data derived from 4 registry-based and 18 non-registry-based studies respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The percentage of referred cases was lower during the pandemic than the percentage of cases pre-pandemic, similar to the findings of a previous report suggesting more symptomatic cases with newly diagnosed breast cancer. 8 , 9 The reason for the reduction may be attributed to the decline in the number of screenings. For the referred cases, the longer pre-visit time of 5.6 days during the pandemic was because of the restricted visits to the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…For several months following the pandemic, patients found themselves repeatedly being told to remain at home unless severely unwell. This necessary and widely issued public health precaution has unfortunately resulted in delayed presentations of several non-COVID related illnesses, including many malignancies [ 1 , 2 , 7 ]. As such, many publications issued recommendations on how services should prioritise the management of different malignancies during the pandemic in order to minimise the impact on patient outcomes [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%